Temperature heterogeneity characteristics in dissimilar friction stir welding between aluminum alloy and magnesium alloy: insights from computational fluid dynamics simulations - Kong, Deshuai; Zhang, Zhao; Shi, Qingyu; Wu, Chuansong; Chen, Shujun; Zhao, Zerui; Yang, Chengle; Qiao, Junnan; Chen, Gaoqiang (International journal of material forming, 2025)
Despite its critical importance in governing the weld strength and residual stress of dissimilar aluminum/magnesium welds by friction stir welding, the in-process temperature characteristics remain a subject of ongoing debate. This paper aims to resolve this debate through computational fluid dynamics simulation with the best accuracy to date, enabled by a state-of-the-art shear boundary model that allows fully coupled analysis of interfacial friction, material flow, heat generation and heat transfer. It is revealed that the temperature on the magnesium side is higher than that on the aluminum side, despite nearly identical total heat generation rates on both sides. This asymmetry is attributed to magnesium’s lower thermal conductivity, which impedes heat conduction. It is interesting to note that the circumferential temperature variation is reduced in high-velocity zones near the tool pin due to enhanced convection. The accuracy of the simulation is rigorously validated via comprehensive comparison between the measured welding temperature and the observed joint macrograph, confirming its capability to resolve the long-standing debate in the in-process temperature characteristics. These insights shed new lights on the thermal processes regarding the dissimilar aluminum/magnesium FSW, offering a foundation for optimizing welding process and weld performance.